Shell model calculations for 18O and 18Ne nuclei. - Almanqoush, Souad S.; Al-Haq, Shams (Libyan Journal of Science &Technology, 2025)
A simple shell model was used to calculate the low-lying energy spectra, reduced electric quadrupole transition probabilities B(E2), and electric quadrupole moments for the oxygen nucleus (18O) and neon nucleus (18Ne). The calculations were performed using computer codes written in the FORTRAN language. Only two identical particles outside a doubly magic core have been considered to occupy the valence single-particle states. The single particle energies were taken from the experimental spectra of 17O and 17F nuclei. The modified surface delta interaction (MSDI) was employed as an effective interaction to calculate the two body matrix elements. The results of previous studies using empirical interactions are also included along with the experimental data to facilitate the comparison. It is found that the results of this work qualitatively compare well with the experimental data, but quantitatively, they are not as good as the previous theoretical works on the same nuclei.